An electrochemically active textile current collector with a high areal capacity and a strong energy recovery effect using an interfacial interaction assembly - Yong, Euiju; Nam, Donghyeon; Kim, Yangsoo; Kim, Kwangsoo; Kim, Byung-Hyun; Ko, Yongmin; Cho, Jinhan (Elsevier BV, 2023)
Conventional current collectors in lithium-ion batteries (LIBs) are generally nonactive components. However, enhancing their electroactive properties and increasing the electroactive surface area can significantly improve the areal energy performance of next-generation battery electrodes. Herein, we introduce an electrochemically active textile current collector that delivers high energy storage performance, achieved through interfacial interaction assembly-induced electroplating. We first prepared metal nanoparticle/multiwalled carbon nanotube multilayer-incorporated cotton textiles using complementary interaction-mediated layer-by-layer assembly, and subsequently electroplated them with Cu. The resulting textile exhibited a high areal capacity of similar to 3.27 mA h cm(-2) at 0.875 mA cm(-2), excellent cycling stability, and a strong energy recovery effect, thanks to the synergistic contributions of the large active surface area of the fibril structure, the robust interfacial assembly, and the formation of a metal oxide NP/pseudocapacitive polymeric gel-like phase at the electrode/electrolyte interface. Moreover, when incorporating Li4Ti5O12 with a theoretical capacity of 175 mA h g(- 1) into our textile current collector, the specific capacity and areal capacity of the LIB anode can be increased up to similar to 573 mA h g(- 1) and 8.60 mA h cm(-2) (at 15 mg cm(-2) LTO), respectively, outperforming those of previously reported LTO-based anodes.